Policy-driven automated reconfiguration for performance management in WDM optical networks. - Golab, W. (IEEE Communications magazine)
A key feature of optical networks based on WDM technology is the ability to optimize the configuration of optimal resources (i.e., wavelengths) with respect to a particular traffic demand. In the broadcast architecture, this involves the assignment of wavelengths to logical links, while in the optically switched architecture it additionally involves the routing of all-optical data paths known as lightpaths. This survey article is concerned with the problem of automatically updating the configuration of an optical network to accommodate changes in traffic demand, which entails making a reconfiguration policy decision, selecting a new configuration and migrating from the current to the new configuration. Existing solutions are classified according to their algorithmic properties, and compared on the basis performance, computational cost, and flexibility. Finally, open problems and research directions are discussed.